2016
DOI: 10.1097/qai.0000000000000856
|View full text |Cite
|
Sign up to set email alerts
|

Lower HIV Risk Among Circumcised Men Who Have Sex With Men in China

Abstract: Background Voluntary medical male circumcision reduces the risk of HIV heterosexual transmission in men, but its effect on male-to-male sexual transmission is uncertain. Methods Circumcision status of men who have sex with men (MSM) in China was evaluated by genital examination and self-report; anal sexual role was assessed by questionnaire interview. Serostatus for HIV and syphilis was confirmed. Results Among1155 participants (242 known seropositives and 913 with unknown HIV status at enrollment), the ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 57 publications
1
14
0
1
Order By: Relevance
“…As the capital of China, Beijing attracts migrants, including MSM, for better employment opportunity and living condition [35]. Previous studies have shown a higher marriage rate among migrant MSM than local MSM [11, 36], explaining why higher prevalence of bisexual behaviors is seen in our study, as well as other Beijing studies (45.6–46.2%) [25, 37, 38]. …”
Section: Discussionsupporting
confidence: 70%
“…As the capital of China, Beijing attracts migrants, including MSM, for better employment opportunity and living condition [35]. Previous studies have shown a higher marriage rate among migrant MSM than local MSM [11, 36], explaining why higher prevalence of bisexual behaviors is seen in our study, as well as other Beijing studies (45.6–46.2%) [25, 37, 38]. …”
Section: Discussionsupporting
confidence: 70%
“…Several studies suggest that a majority of MSM in large cities are migrants (61.8%-81.3%) (Lau, Li, Wang, & Lai, 2015; D. Li et al, 2012; Liu, Ruan, et al, 2015; Qian et al, 2015). Compared to non-migrant MSM, migrant MSM are more likely to have a dynamic sexual network and engage in risky behaviors (Liu et al, 2012; Song et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with a lower per-act risk for HIV-1 transmission via IAI, compared with the risk via RAI,[31] and may also result from a protective effect of circumcision during IAI. [32]…”
Section: Discussionmentioning
confidence: 99%